Application of Multi-Criteria Decision Making Techniques in Time-Cost-Quality Trade-Off - Monghasemi, Shahryar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Discrete time-cost-quality trade-off problems (DTCQTPs) are a branch of project scheduling problem which deals with establishing a compromise between time, cost and quality. In this thesis, multi-objective optimization models, namely, genetic algorithm (GA) and improved harmony search (IHS), integrated with multiple criteria decision making (MCDM) methods are developed to solve the DTCQTPs with the aim to find the best optimal project scheduling alternative. Three different MCDM methods, e.g., evidential reasoning (ER), PROMETHEE, and TOPSIS are used to rank the Pareto-optimal solutions obtained through GA and IHS. The proposed methodology is applied to a benchmark construction project scheduling problem to investigate the efficiency of the proposed methods. The obtained results revealed that the ER approach which is a more complex MCDM methods when compared with PROMETHEE and TOPSIS can provide the DMs with a transparent view of each project scheduling alternative. Thus, detailed investigations is possible for the ER approach, while the PROMETHEE approach with a similar ranking of the solutions can be a useful substitution for the ER approach. The performance analysis showed that IHS algorithm is more efficient than GA while the former has a higher computational time. Keywords: discrete time-cost-quality trade-off problem (DTCQTP), multi-objective optimization models, genetic algorithm (GA), improved harmony search (IHS), multiple criteria decision making models, evidential reasoning (ER), PROMETHEE, TOPSIS.

Ayrık zaman-maliyet-kalite ilişkileri problemleri (AZMKP), zaman, maliyet ve kalite arasında bir uzlaşma kurulması ile ilgili proje planlama problemi dalından biridir. Bu tezde, çok amaçlı optimizasyon modelleri, yani genetik algoritma (GA) ve geliştirilmiş uyum arama (GUA), çok kriterli karar verme (ÇKKV) yöntemleri ile entegre olarak en iyi optimum proje planlama alternatifini bulmak amacıyla ZKMP’ni çözmek için geliştirilmiştir. Üç farklı ÇKKV, örneğin kanıta dayanan muhakeme (KDM), PROMETHEE ve TOPSIS, GA ve GUA ile elde edilen Pareto-optimal çözümlerini sıralamak için kullanılır. Önerilen metodoloji, yöntemlerin etkinliğini araştırmak için bir kıyas inşaat projesi planlama sorunu üzerine uygulanır. Elde edilen sonuçlar, PROMETHEE ve TOPSIS’e kıyasla daha karmaşık bir ZKMP yöntemi olan KDM’nin karar vericilere (KV) her bir proje planlaması alternatifinin şeffaf görünümünü sağladığını ortaya çıkarmıştır. Böylece, PROMETHEE yaklaşımı, benzer bir sıralama çözümleri ile KDM yaklaşımı için yararlı bir ikame olabilir iken, GUA yaklaşımı için detaylı incelemeler mümkündür. Performans analizi, eskisinin daha yüksek hesaplama süresine sahip iken, GUA algoritmasının GA’dan daha verimli olduğunu göstermiştir. Anahtar kelimeler: Ayrık zaman-maliyet-kalite ilişkileri problemleri (AZMKP), çok amaçlı optimizasyon modelleri, genetik algoritma (GA), geliştirilmiş uyum arama (GUA), çok kriterli karar verme modelleri, kanıta dayanan muhakeme (KDM), PROMETHEE, TOPSIS.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assoc. Prof. Dr. İbrahim Yitmen.
Keywords: Civil Engineering; Production scheduling; discrete time-cost-quality trade-off problem (DTCQTP), multi-objective optimization models, genetic algorithm (GA), improved harmony search (IHS), multiple criteria decision making models, evidential reasoning (ER), PROMETHEE, TOPSIS.